Trajectory and spreading of falling circular dense jets in shallow stagnant ambient water - Hossein Azizi Nadian; Nima Shahni Karamzadeh; Javad Ahadiyan; Morteza Bakhtiari (Results in Engineering)
This study investigates the trajectory and spreading of a horizontal circular dense jet flow discharged above the water surface, the flow of which falls into shallow stagnant ambient water. For this purpose, 27 experiments were performed using three diameters, flow rates, and falling heights to investigate jet trajectory. In addition, nine experiments with constant falling height were conducted to study jet spreading. The densimetric Froude number of the jet flow at the nozzle outlet and water surface of the present study ranged from 0.72 to 4.22 and 36.96 to 86.10, respectively. The data pertaining to this study were extracted and analyzed through image processing. The results of the experiments showed that by increasing both the momentum and falling height, the trajectory of the jet flow reached a farther distance from the discharge nozzle. The spreading of the outer boundaries of the dense circular falling jet flow tended to extend downstream of the impact point and had an elliptical motion on the bed. The relationship between radial distance from the impingement point to the outer boundary of flow and time was determined to have a power of 0.67 for flow along the flume and 0.59 for flow along the flume's width.